Analisis Ketahanan Pangan Rumah Tangga Berdasarkan Proporsi Pengeluaran Pangan Dan Konsumsi Energi (Studi Kasus Pada Rumah Tangga Petani Peserta Program Desa Mandiri Pangan Di Kecamatan Indrapuri Kabupaten Aceh Besar) - Agustina Arida; Sofyan Sofyan; Keumala Fadhiela (Jurnal Agrisep, 2015)
ABSTRACT. The achievement food security of household indicated their success for food security nationally, regionally and locally. The proportion of food output and energy consumption is an important indicator in determining the household food security. The purpose of this study was to know how large a proportion of food expenditure, the level of of energy consumption and the condition of the household food security of farmers in DEMAPANProgram in Indrapuri Sub-district Aceh Besar Regency. This research was held in the Indrapuri sub-district by using purposive sampling method. Data were analyzed by methods of analysis of income and expenditure of farmer household, income and exenditure of farmer household, consumption, and cross indicator of household food security. The result show that: (1) The average farm income of rice paddy is Rp 1.885.517,00 per growing season and the average of expenditure of household farmer is Rp 1.411.500,00 per month (2) The level of energy consumption and protein is 62,19% and 81,23% (3) The condition of household food security of Farmer less and deficits.